Los cuatro libros de la arquitectura - Palladio, Andrea, 1508-1580; Palladio, Andrea, 1508-1580.; De Aliprandini, Luisa; Martinez Crespo, Alicia (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2008)
Renaissance architect Palladio was one of the most influential figures the field of architecture has ever produced. Of even greater significance than his buildings is this treatise, one of the most important books in the literature of architecture.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed May 13, 2016)
Keywords: Architecture -- Early works to 1800.; Rome -- Antiquities -- Early works to 1800.; Electronic books